TEACHING STAFF TRAINING, HIGHER SCHOOL PEDAGOGY, AND ENGINEERING PEDAGOGY: ROUND TABLE DISCUSSION - Editorial Article (Высшее образование в России)
The 6'h annual International and regional IGIP conference and a methodological seminar of the State Technical University - MADI took place on March 18, 2016. Within the framework of the conference the journal Vysshee obrazovanie v Rossii [Higher Education in Russia] has conducted a workshop. Area of discussion - "Teaching Staff Training, Higher School Pedagogy, and Engineering Pedagogy". The participants were the members of the Editorial Board and the experts in teaching personnel training and in professional pedagogy. There are presented the participants' reports on the panel discussion.